Economic factors - Sushentseva O. V. (Interactive science, 2019)
oil production has long been considered the major source of replenishment of the budget of the country and the starting point for the development of other industries so today the efficiency of the oil complex functioning of the Russian Federation and its investment attractiveness is a key problem for the state. In this article the author focuses attention on factors that one way or another form picture of development and on this foundation obtains data for the econometric model.
Keywords: экономика; инфраструктура; промышленность; факторы; нефть; Россия; нефтедобыча; Russia; industry; economy; factors; infrastructure; oil; нефтяной комплекс; oil production; oil complex